Do managers reappoint auditor for related party transactions? Evidence from selected East Asian countries - Mohd Mohid Rahmat,; Siti Hajar Asmah Ali, (Penerbit Universiti Kebangsaan Malaysia, 2016)
We study the association between auditor reappointment (initial relationship stage), including recurring auditor appointment over several consecutive years (close relationship stage) and company engagement in related-party transactions (RPTs) for selected listed companies from Hong Kong, Malaysia, Singapore and Thailand. The results show that auditor reappointment has significant and negative associations with company engagement in RPTs. By contrast, the close ACR relationship increases company engagement in RPTs. The evidence also suggests that Big 4 audit firms can reduce company engagement in RPTs, even when they have a close relationship. However, the findings derived from a sub-sample of RPT companies suggest that the close relationship between Big 4 audit firms and their clients substantially encourages companies to engage in RPTs. Overall, these findings are consistent with theories in which higher audit quality is effective at monitoring RPTs, but the established relationship looks likely to create conflicting opinions that impair auditors’ independent judgment. Nevertheless, the likelihood of conflict disappears when clients operate in countries that more effectively implement and enforce regulations and protect minority shareholders.